Change in storage enzymes activities in natural and accelerated aged seed of wheat (Triticum aestivum) - CHAUHAN, D S; DESWAL, D P; DAHIYA, O S; PUNIA, R C (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2006â€“10 on seed of six varieties of wheat (Triticum aestivum), viz C 306, PBW 502, WH 542, WH 711, WH 283 and RAJ 3765 were subjected to natural vis-Ã -vis accelerated ageing conditions and evaluated for change in storage enzymes activities in natural and accelerated aged seed of wheat. The present investigation revealed that the level of various antioxidant enzymes have been studied so as to find the exact cause of seed deterioration. The activity of all the antioxidant enzymes, viz catalase, peroxidase, dehydrogenase and amylase decreased after natural and artificial ageing treatment in all the varieties. Among different ageing treatments, the dehydrogenase activity was recorded less in natural as well as accelerated aged seed lot as compared to fresh lot. In natural aged seed lot catalase and peroxidase activities decreased as the ageing progressed in all the six varieties the rate of decreasing of both the enzymes activity was higher after 18 months of storage. A gradual decline in amylase activity was reported in natural aged seed lot in all six varieties. Dehydrogenase activity was maximum up to 14 months of storage and after that it declined in terms of absorbance among all the varieties. It decreased at faster rate after 18 months of storage.